1997
DOI: 10.1111/j.1471-0528.1997.tb10655.x
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital ageing and its effect on sexual health in older British women

Abstract: Objective To provide information on the extent of problems of urogenital ageing in older British women. were currently affected by individual symptoms; however, these were often of long duration. The majority (73%) were not sexually active, with lack of a partner being a factor for many. There was also a decreasing prevalence of sexual activity with increasing age. Those sexually active in the 65-74 year old age group (n = 148) tended to have a similar sexual frequency (at least once per month) compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
10

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 9 publications
2
65
0
10
Order By: Relevance
“…In total, 6% of Moroccan 33 and Swedish 17 women reported some degree of vaginismus, which did not appear to be related to age. The prevalence of dyspareunia was reported as low as 1% in Australian women 34 and 2% in elderly British women, 35 whereas other studies found that dyspareunia was present in as many as 14% to 27% of women. 16,18,19,26,27,32 Several investigations described increasing dyspareunia with increasing age.…”
Section: Dyspareunia and Vaginismusmentioning
confidence: 95%
“…In total, 6% of Moroccan 33 and Swedish 17 women reported some degree of vaginismus, which did not appear to be related to age. The prevalence of dyspareunia was reported as low as 1% in Australian women 34 and 2% in elderly British women, 35 whereas other studies found that dyspareunia was present in as many as 14% to 27% of women. 16,18,19,26,27,32 Several investigations described increasing dyspareunia with increasing age.…”
Section: Dyspareunia and Vaginismusmentioning
confidence: 95%
“…[4][5][6][7][8][9][10][11][12] The prevalence of the male sexual problems of erectile dysfunction and early ejaculation and their related risk factors have been investigated most extensively, whereas fewer studies have focused specifically on female sexual dysfunction. 13,14 Moreover, relatively little is known about the average frequency of sexual activity and the importance of sexual relationships among older men and women, although the few studies that have examined sexuality in mature adults have reported that sexual interest and activity persist well into older age. 15,16 The published studies of the prevalence and correlates of sexual problems in developed and developing countries have used a variety of different study designs and definitions, which makes valid cross-national comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] The prevalence and correlates of the male sexual disorders of erectile dysfunction and early ejaculation have been studied most extensively, while fewer investigations have looked specifically at female sexual problems. 16,17 Furthermore, relatively little has been reported about the usual frequency of sexual activity and the value and significance of sexual relationships for older individuals, although the few published studies in this area have concluded that sexual interest and activity persist well into older age. [18][19][20] The published literature on the prevalence and correlates of sexual disorders comprises studies conducted in developed and developing countries that have employed a wide variety of study designs and definitions.…”
mentioning
confidence: 99%